Performance-based identity in a BIM environment : An architect’s perceptions and experiences - Syafizal, Shahruddin; Mohd, Zairul; Ahmad Tarmizi, Haron; Meor Mohammad, Fared (Emerald Publishing, 2022)
Interpreting the meaning structure of architects' actions, behaviours and performances enacted in a building information modelling (BIM) environment is implausible by returning to the classic and ideal imagery of an architect as a natural leader. Yet, little has been empirically explored on how architects perceive their identity and most critically, how they act, behave and perform their way into it in such an environment. Consequently, architects' failing to adapt their core identity to the varying circumstances may lead to their irrelevance and being side-lined merely as aesthetic building surgeons. The current study therefore seeks a better understanding of their perceptions and experiences in manifesting their identities in the phenomenon. Design/methodology/approach: Drawing upon the interpretive phenomenological approach, ten architectural trained individuals were selected for in-depth, semi-structured interviews, and written accounts exercise to disclose their lived experience. The study was conducted in a Malaysian architectural consultancy practice (ACP) setting. Findings: The data analysis resulted in the following five performance identity themes that revolve around the core identity of a successful designer: “performing as a design strategist”, “performing as a design translator”, “performing as a design facilitator”, “reinstating the identity of a design coordinator” and “performing as a design innovator”. Practical implications: The study serves as groundwork for professional institutional bodies to further reconstruct a career road map alongside the professional development framework towards elevating, developing and facilitating the hybridity of architects' performance identities in such environment. Social implications: The study serves as a groundwork for professional institutional bodies to reconstruct the existing continuing professional development (CPD) programmes, materials and framework so that they reflect the performances of future architects practicing in a BIM environment. The elicited experiences may also inform architectural curriculum designers of the appropriate approaches of teaching and learning in architecture that could promote the hybridity of architects' performance identities in such an environment. Originality/value: The study contributes to the identity literature by yielding valuable new insights about the experiences and behaviour of architects practicing in a BIM environment. Understanding such complexity would not be possible merely based on the theoretical lenses of professional identity and organisational identification as adopted in previous studies.